The Impact of Kite and Bird Activities on the Management of the Aviation Operational Safety Area (KKOP) at I Gusti Ngurah Rai International Airport, Bali - Dewa Putu Gerdha Pradiptha Sidan; Dewanti; Taqia Rahman (International journal of technology and education research, 2026)
This study examines the impact of kite activity and bird strikes on the management of the Aviation Operational Safety Area (KKOP) at I Gusti Ngurah Rai International Airport, Bali. The study aims to analyze aviation safety risks, evaluate the effectiveness of mitigation strategies, and identify obstacles to implementing aviation safety policies in the KKOP area. The study used a mixed methods approach with an explanatory design. The study population included the airport safety unit, AirNav Indonesia, the Airport Authority Region IV, and the community around the airport. The sample was determined using purposive sampling. Data collection was conducted through semi-structured interviews, documentation, and aviation incident reports for the period 2020–2025. Data analysis used descriptive statistics, Hazard Identification and Risk Assessment (HIRA), thematic analysis, and SWOT analysis. The results showed that bird strikes were more dominant than kite disturbances, with the highest risk occurring in the runway, taxiway, and apron areas during the takeoff and landing phases. The threat of kites was influenced by socio-cultural factors of the community, while bird strikes were influenced by environmental conditions around the airport. This study concludes that integrated preventive, regulatory, technological, and collaborative strategies are needed to improve aviation safety management and support the zero accident target.